Hubungan Struktur Pasar dan Perilaku Pasar Serta Pengaruhnya Terhadap Kinerja Pasar - P. Eko Prasetyo (Universitas Islam Indonesia, 2007)
The objective of this research are to analyze the model of the correlation between mar¬ket structure and market conduct and their effects on the market performance. This re¬search was conducted by using the survey method on 112 households of respondent samples of bamboo crafts makers from 625 household population bamboo craft makers in Bantul subdistrict, the Province of Special District of Yogyakarta. The sampling technique used in this research is two steps of cluster random sampling technique, and the analysis models used are the industrial organization and simultant system regression-correlation model.The result of the research shows that is a tight and positive correlation between market structure and market conduct on the market performance, that is 98,26% and the significant effects between market structure and market conduct on market performance in the amount of 96,55%. The market structure as the key of market conduct and market performance is in the form of unconcentrated-market structure, because the value of CR-4 and CR-8 is in the amount of 18,91% and 27,71% and it is likely as the form of monopolistic competition market structures. This unconcentrated market structure in the form of pushes the market conduct of the bamboo craft makers to be comfortable to use the pattern of strategy conduct of non-price competition and “tuna satak-bati sanak” principle instead of using the price-competition conduct. It means that the business based on that the principle, and get the additional customers and normal profits in the long-term instead of using price-competition that can kill their business. The research result shows that the market performance that is evaluated by using the levels of profitability, productivity, and efficiency generally is still low. The marketing factor is the production factor that most dominantly effects the market performance.Keyword: Market structure, market conduct and market performance.